2017
DOI: 10.1177/1687814017703896
|View full text |Cite
|
Sign up to set email alerts
|

In-plane dynamic crushing and energy absorption capacity of self-similar hierarchical honeycombs

Abstract: The in-plane dynamic crushing behavior and energy absorption capacity of self-similar hierarchical honeycombs under different impact velocities are numerically studied using ANSYS/LS-DYNA. First, the hierarchical honeycomb models with uniform cell-wall thickness are constructed by replacing every three-edge structure nodes of a regular honeycomb with smaller self-similar hexagons of the same orientation. The respective influences of hierarchical parameters, bulk materials, and impact velocities on the macro-/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…As mentioned in section ''Most appropriate strain,'' all s-e curves have four different phases: linear elastic phase, yield phase, flat plateau stress phase, and densification phase, which are similar to the curve patterns of other 2D honeycombs, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] even though the s-e curves have different characteristics at different crushing velocities. Mean quasi-static and dynamic plateau stresses are discussed in detail in section ''Mean plateau stress.''…”
Section: Reliability Of Fe Modelmentioning
confidence: 63%
See 1 more Smart Citation
“…As mentioned in section ''Most appropriate strain,'' all s-e curves have four different phases: linear elastic phase, yield phase, flat plateau stress phase, and densification phase, which are similar to the curve patterns of other 2D honeycombs, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] even though the s-e curves have different characteristics at different crushing velocities. Mean quasi-static and dynamic plateau stresses are discussed in detail in section ''Mean plateau stress.''…”
Section: Reliability Of Fe Modelmentioning
confidence: 63%
“…Owing to the advantages of FE simulations over experiments, the FE numerical method has been solely and widely used in the investigations of 2D honeycombs. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] The existing investigations have shown that the configuration parameters and crushing velocity affect the dynamic behaviors of 2D honeycombs. The typical configuration of the MRACHs (with 9 3 9 cells in directions x 1 and x 2 ) is shown in Figure 1 In this article, the in-plane (direction x 2 or x 1 in Figure 1) crashworthiness of MRACHs is investigated numerically using the explicit FE analysis software, ANSYS/LS-DYNA, at the crushing velocities 1-250 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the effects of the cell orientation angle and the cell size on the mechanical properties were explored [16][17][18] . So far, there have been a considerable number of studies on the crushing behaviors of regular honeycombs, especially for the regular hexagonal honeycombs, with theoretical, numerical and experimental methods [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…For regular and irregular hexagonal grids and circular grids, a number of researches have been conducted. In recent years, increasing interest has been paid to the novelcell grids and the composite grids which show enhanced EA capacity [18][19][25][26][27] . Although there exist considerable theoretical and numerical studies for the type grids [28][29][30][31][32] , few efforts are paid to the effect of orientation parameters on the initial peak force and the EA for the square-cell grids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation